Volunteer Activity Tracking System (VATS) - Nur Farahhana Rozali,; Nurul Fatin Shahira Rahim,; Rafidah Abd Razak, (Multidisciplinary Applied Research and Innovation, 2023)
Prihatin Kedah is a Kedah based non-governmental organization (NGO) that rely extensively on volunteers to achieve the NGO’s goals. The purpose of this project is to develop a Volunteer Activities Tracking System (VATS) that are capable of tracking the volunteers’ activities, and can also provide an intermediary between NGO’s administrator and volunteers. All the volunteer activities are currently handled manually through the phone via WhatsApp. Volunteers have difficulties to keep track and view the schedules of events, activities, and locations. In addition, volunteers also face difficulties to communicate with the NGO’s admin to get updates of events and activities. The second problem is that it takes a lot of energy and required a lot of time to produce and generate report since they have to do it manually. They need to retrieve back and keep track of all the documents to find the information to produce a report which often lead to other problems such as duplication in data entry, data not accurate and others. The objective of the system is to serve as a platform to manage volunteer activities, to provide efficient way to track volunteer activities and to manage the process of volunteer activities easier for both volunteer and admin. Waterfall model is used in system development life cycle (SDLC) in this project which include phases of planning, analysis, design, testing, deployment and maintenance. With the system, availability of volunteers is matched with events, activities and location. Thus, allowing easy coordination of volunteers and admin also able to generate the report more accurately.  The system effectively match the volunteers’ preferences with the NGO’s needs. Making admin task easier as the system provide a single platform to manage activities and produce report. Hence, this project provide a positive social impacts of the use of digital solution for community well-being.